Intestinal infections and probiotics - Bednarek, Jadwiga Janina (Journal of Education, Health and Sport, 2018)
The creator of the concept of probiotic - increasing the amount of bacteria beneficial to the body - was Miecznikov. In Poland in 1899, Brudziński described for the first time the treatment with lactic acid-producing bacteria, which later became the "probiotic". Research on the influence of these bacteria on the organism has shown many health effects over the last 20 years, including: prevention and support of intestinal infections, immune stimulation, restoration of eosinophilia, and inhibition of carcinogenesis. The effectiveness of probiotics depends on the type of strains. The article presents the importance of probiotic strains in supporting the treatment of gastrointestinal diseases on the basis of the literature. The probiotic strains contained in medicinal preparations have efficacy in the treatment of infectious diarrhoea in children, intestinal functional disorders and intestinal resistance regulation. They can be used in inflammatory bowel diseases to achieve remission. Not all products containing certain probiotic strains reduce the risk of post-antibiotic diarrhoea. Probiotics are generally considered safe for the body but in certain health situations they may have a negative impact.